Artificial Intelligence, Big Data, and Internet of Things for Sustainable Industry and Infrastructure Development - Singh, Rajesh; Kumar, Rakesh; Khanna Malhotra, Rupa (Bentham Science Publishers, 2026)
Artificial Intelligence, Big Data, and Internet of Things for Sustainable Industry and Infrastructure Development explains how AI, IoT, Big Data, and Blockchain reshape industries by enabling real-time monitoring, improving resource efficiency, predicting climate risks, and strengthening ethical decision-making in sustainable infrastructure and smart industrial systems. The book connects digital innovation with responsible business and healthcare practices, showing practical uses in waste reduction, supply chain sustainability, disaster forecasting, traffic automation, online safety, and trust-building systems for digital markets. Key Features - Reduce production waste using big data analytics - Boost operational efficiency and lower industrial costs - Predict climate risks using AI and historical datasets - Authenticates e-commerce reviews using ML and NLP - Decentralised digital industries using blockchain systems - Optimises sustainable supply chain logistics with data science - Forecasts natural disasters for smart cities using AI models - Improves disaster resilience using fractal and fractal-based analysis - Automates adaptive traffic signalling using Arduino and IR sensors - Detects cyberbullying using AI for faster moderation